2018
DOI: 10.1007/s10995-018-2428-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sociodemographic Characteristics, Experiences and Health Behaviors Associated with Postpartum Care Utilization: Evidence from Maryland PRAMS Dataset, 2012–2013

Abstract: Objectives Postpartum visits are increasingly recognized as a window of opportunity for health care providers to counsel new mothers and promote healthy behaviors, including increasing contraceptive use and screening for postpartum depression. In Maryland, there is a lack of research on postpartum visit (PPV) attendance and the specific risk factors associated with not receiving postpartum care. In this study, we estimated the proportion of mothers in Maryland who attended a PPV and assessed maternal sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…This study which focused on the specific group of adolescent mothers found inadequate number of antenatal visits, being single/separated/divorced and lower level of education significantly associated with loss to post‐partum follow‐up. Previous studies also found that being unmarried and inadequate number of antenatal visits (<5 visits) were risk factors for non‐attendance to the post‐partum visit. In a study involving healthy women, higher level of education was identified as a factor associated with post‐partum visit which was consistent with our finding.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This study which focused on the specific group of adolescent mothers found inadequate number of antenatal visits, being single/separated/divorced and lower level of education significantly associated with loss to post‐partum follow‐up. Previous studies also found that being unmarried and inadequate number of antenatal visits (<5 visits) were risk factors for non‐attendance to the post‐partum visit. In a study involving healthy women, higher level of education was identified as a factor associated with post‐partum visit which was consistent with our finding.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies also found that being unmarried and inadequate number of antenatal visits (<5 visits) were risk factors for non‐attendance to the post‐partum visit. In a study involving healthy women, higher level of education was identified as a factor associated with post‐partum visit which was consistent with our finding.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations